(untitled) (Research, Society and Development, 2022)
Introduction: The skin is divided into three layers, the epidermis, the outer layer with a thickness of 0.07 to 0.12 mm, divided into stratum corneum (skin surface), stratum lucid, stratum granulosum, stratum spinosum and basal or germinal stratum, it is in this layer that constant cell renewal occurs, initially the cells are elongated and flatten as they age and consequently migrate to the underlying layers. Objective: To present the best chemical peeling in dyschromias caused by acne. Method: This is a literature review, a survey was carried out in the VHL using the DeCS: melanin, chemical peeling, dyschromias. Including articles from 2012-2022. Result: Acne is a disease of the pilosebaceous units of the skin. An altered keratinization pattern in the hair follicle leads to blockage of sebum secretion. Final Considerations: Chemical peels have varying degrees of effectiveness, but an overall positive result. Each technique has advantages and cons.